Continuous wave Nd:YAG laser photocoagulation in proliferative diabetic retinopathy. Issue 7 (July 1995) - Menchini, U; Lanzetta, P; Soldano, F; Ferrari, E; Virgili, G
Abstract : AIMS–The therapeutic efficacy of the continuous wave (CW) Nd:YAG laser (working in the free running mode) was investigated in proliferative diabetic retinopathy (PDR) comparing it with a conventional laser source such as the krypton laser. METHODS–Twenty four eyes of 12 patients affected with bilateral PDR were included and divided in two groups. The right eyes were treated with a red krypton laser and the left eyes with a CW Nd:YAG laser. RESULTS–Three months after krypton photocoagulation 10 eyes showed a reduction or a complete regression of PDR and two eyes were unchanged. In the CW Nd:YAG laser group no eyes showed any regression of new vessels, in seven eyes the angiographic features were unchanged, and in five eyes they worsened. All the eyes of the second group underwent retreatment with the krypton laser after 3 or 6 months. After a mean follow up of 13 months all eyes in the krypton group showed a reduction or complete regression of PDR; in the retreated group 10 eyes improved and two were unchanged. CONCLUSIONS–The statistical analysis showed a highly significant difference (p = 0.001) between krypton and CW Nd:YAG laser which indicated the lack of efficacy of the latter in the treatment of PDR. In the krypton laser group no significant difference (p = 0.05) after the retreatment was found confirming the efficacy of this treatment.